Pre-lacteal feeding practices in a rural area of Bangladesh - Tarannum, Sabah; Hyder, S.M. Ziauddin; Chowdhury, AMR (BRAC Research and Evaluation Division (RED), 2019)
This study aims to describe the nature and extent of pre-lacteal fluid and colostrum feeding practices in a rural community of Bangladesh and also to investigate the mothers level of knowledge in relation to hygiene and safety related to the feeding practices. The data were obtained from 473 mothers with infants aged less than 24 months from 14 villages of Matlab thana from April to August 1995. A total of 2076 households were visited to obtain the above number of the eligible mothers. The households were categorized into two groups based on their socioeconomic status, i.e., BRAC eligible or poor and non-eligible or non-poor. The survey revealed that about 93% of the infants received pre-lacteal liquid and only 7% received breast milk as the first liquid. Honey or honey with water was the most frequently given pre-lacteal liquid followed by mustard oil, which they believed, would clean the baby's mouth. Surprisingly, around 12% of the infants did not receive any nutritious liquid except for plain water until 24 hours after birth. About 3 5 and 44% of the mothers in BRAC eligible and non-eligible households respectively mentioned that giving honey before initiation of breast feeding was their tradition. Among the BRAC eligible households, 22% of the mothers stated that insufficient milk secretion immediately after delivery was the reason to give pre-lacteal liquid. A majority of the mothers stated that finger, in most instances without washing, was used to introduce the liquid in the baby's mouth. Frequency of finger use was higher among the BRAC eligible compare to non-eligible households. Grand mothers were the initiators of pre-lacteal liquid in about 47% instances followed by the birth attendants, 25%. Sixty two percent of the infants among BRAC eligible and 76% among the non-eligible households received colostrum. Mothers from both BRAC eligible and non- eligible households seemed to have adequate knowledge about colostrum feeding in terms of its beneficial effects on infants' health. They mentioned that colostrum was a nutritious liquid, which provide_d . required nutrients and protected the babies against infections. In conclusion, pre-lacteal feeding was highly prevalent in the villages of Matlab thana, which perhaps a common feature in other rural areas of Bangladesh. In most of the cases, women's lives, increased income/livelihood security, fertility control, increased nutritional status, decreased morbidity and decreased mortality (7). Improved nutritional status was identified as one of the important components of human well-being.